Usage of Alternative Medicine in Cancer Patients - Moolasarn, Summana; Sripa, Saksit; Chaisila, Charuntorn; Chuechom, Nampueng; Sankarn, Saowanee; Kuesirikiet, Vichittra; Sutawee, K; Hausary, Jeerasak (Siriraj Medical Journal, 2003)
The purpose of this study was to find out the characteristics of alternative medicine (AM) use and factors related to its use such as expense, compliance, and quality of life in 180 cancer patients from Suppasitthiprasong Hospital and the Center of Cancer Prevention and Control in Ubon Ratchathani. Results from questionnaires indicated that 77% of cancer patients used AM, mostly herbal medicine either in altered or unaltered from, because they received advice from other persons and wanted to obtain extra treatment. Patients who used AM still maintained good compliance with their conventional treatment. However, 51.35% of patients were using both alternative and conventional medicine without telling their doctors. The mean expense for AM us was 451 Baht per patients per month. Thus, if the percentage of AM use and their costs are true for other Thai cancer patients throughout Thailand, AM use expenditure for the whole country would be about 112 millions Baht per month, which is quite high. After controlling for other factors, results also indicated that patients with low education (primary grade or lower) were significantly more likely to use AM than those patients with higher education (high school or higher) (OR = 0.04, p = 0.007). Unemployed patients were significantly more likely to use AM than those patients who were farmers (OR = 0.04, p = 0.007). Patients who suffered from side effects of conventional therapy were significantly more likely to use AM than patients who did not (OR = 3.05, p = 0.005). In addition, patients without problems with daily life due to cancer pain were significantly more likely to use AM than those who had no emotional problems (OR = 0.98, p = 0.004). However, there were no other differences in other dimensions of quality of life. There are some limitations in this study preventing generalization to other Thai people such as the lack of information concerning the patients' diagnosis and stage of cancer, differences in cultures and belief, and the AM cost.